EXPRESSION PROFILE OF EARLY PREGNANCY MARKER GENES (OAS-1 AND MX-2) AND SERUM CONCENTRATION OF MX-2 PROTEIN IN JERSEY CROSSBRED COWS - A.G. Nithin; T. Sarath; K. Vijayarani; K. Krishnakumar; N. Arunmozhi; C. Pugazharasi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In the present study, the expression pattern of OAS-1 and MX-2 gene in peripheral blood mononuclear cells (PBMC) was associated with the early pregnancy in cattle. A total of 60 animals were selected and divided into 2 groups, treatment (50) and control (10) group and synchronized using double PGF2α protocol by 11 days apart followed by insemination at 72 and 96 hrs after second dose of PGF2α. The cows were subjected to blood collection on day 0, 14, 18, 20 and 25 post insemination and Peripheral Blood Mononuclear Cells (PBMC) were harvested using Histopaque® solution, followed by RNA isolation and cDNA synthesis. A significantly (P≤0.01) higher expression of OAS-1 and MX-2 gene was observed on days 18 and 20 post oestrum by quantitative real-time PCR and concentration of MX-2 protein in serum were significantly higher (P≤0.05) on day 18, 20 and 25 in pregnant cows when compared with that of non-pregnant cows. Hence, the present study is concluded that the expression of OAS-1 and MX-2 genes and their encoded proteins may be used to develop a marker for early pregnancy diagnosis in cattle.